DksA plays an essential role in regulating the virulence of Borrelia burgdorferi. Issue 1 (14th April 2020) - Mason, Charlotte; Thompson, Christina; Ouyang, Zhiming
Abstract: The RNA polymerase‐binding protein DksA, together with the alarmone nucleotides (p)ppGpp, mediates the stringent response to nutrient starvation in Borrelia burgdorferi . To date, the contribution of DksA to B. burgdorferi infection remains unknown. We report here that DksA is essential for B. burgdorferi to infect a mammalian host. dksA expression was highly induced during infection. Moreover, a dksA ‐deficient mutant was incapable of infecting mice. The mutant displayed growth defects when cultured in vitro and resistance to osmotic pressure was markedly reduced. These phenotypes were fully restored to those of the wild type when dksA mutation was complemented. We further showed that DksA controlled the expression of virulence‐associated lipoprotein OspC, likely via the central alternative sigma factor RpoS. Synthesis of RpoS was abolished in the dksA mutant, but rpoS transcription remained unaffected. Additionally, we found that the expression of clpX, clpA, clpP, and clpP2 was significantly increased in the mutant, suggesting that DksA may post‐transcriptionally regulate rpoS expression via its effect on ClpXP and/or ClpAP proteases. These combined data demonstrate that DksA regulates B. burgdorferi virulence at least partially through its influence on RpoS and OspC. This study thus elucidates that, in addition to function as a stringent response regulator, DksA promotes the transcription and/or translation of genes contributing to B. burgdorferi infectivity. Abstract : Borrelia burgdorferi utilizes numerous strategies to survive in ticks and mammalian hosts. In this study, we report an essential role of DksA in the infection of B. burgdorferi . The loss of DksA not only impairs bacterial growth and resistance to osmotic pressure, but also renders the bacterium incompetent to infect mice. We also found that DksA regulated the synthesis of RpoS, which provides new insights into another regulatory layer controlling RpoS in B. burgdorferi .